Organised Tawarruq in Islamic Law - Abdul Rahman, Zaharuddin (Red Money, 2011)
The renowned Muslim economist Prof. Nejatullah Siddiqi lists the harmful effects of tawarruq. He also dictates that the approval of tawarruq may benefit individuals. However, if this is practised on a large scale, it would result in the proliferation of debt in the society, which would bring macroeconomic instability.Thus, before deciding on the Sharīʿah compliance of such a product, the Sharīʿah Advisory Board of any Islamic financial institution must take into account the macroeconomic consequences of approving the product. This article screen through the claims by providing different view especially from Fiqhi perspectives.